Implementation of an Artificial Intelligence Algorithm for sepsis detection - Luciana Schleder Gonçalves; Maria Luiza de Medeiros Amaro; Andressa de Lima Miranda Romero; Fernanda Karoline Schamne; Jacson Luiz Fressatto; Carolina Wrobel Bezerra (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to present the nurses' experience with technological tools to support the early identification of sepsis. Methods: experience report before and after the implementation of artificial intelligence algorithms in the clinical practice of a philanthropic hospital, in the first half of 2018. Results: describe the motivation for the creation and use of the algorithm; the role of the nurse in the development and implementation of this technology and its effects on the nursing work process. Final Considerations: technological innovations need to contribute to the improvement of professional practices in health. Thus, nurses must recognize their role in all stages of this process, in order to guarantee safe, effective and patient-centered care. In the case presented, the participation of the nurses in the technology incorporation process enables a rapid decision-making in the early identification of sepsis.